Development of Numeracy Literacy-Based Math Problems in a Personal Context for Middle School Students - Sektiwulan, Adelia; Nindiasari, Hepsi (STKIP Singkawang, 2024)
Numeracy literacy is one of the types of literacy included in GLN, which stands for the National Literacy Movement. Numeracy literacy skills are also necessary to face the challenges of the digital and information era, but according to PISA results, Indonesia's numeracy literacy skills are still below the international average. Therefore, this study aims to develop mathematics problems based on numeracy literacy in personal contexts for junior high school students. This research is an R&D study using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The questions developed were validated by 2 validators and can be categorized as valid. The valid problems were tested on 34 eighth-grade students in one of the junior high schools in Serang Regency. The test results in the form of quantitative data were calculated using Anates V4 to measure validity, reliability, and difficulty level. The results showed that two multiple-choice questions and two essay questions were valid and reliable, while one complex multiple-choice question was found to be invalid.